2019
DOI: 10.3390/su11205782
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Strategic Human Resource Management Practices on Competitive Advantage Sustainability: The Mediation of Human Capital Development and Employee Commitment

Abstract: Academic institutions like other business organizations strive to achieve, maintain, and sustain their competitive advantages. In this study, we examined the influence of the “strategic human resources management (HRM) practices” on the achievement of “competitive advantages” that will be sustainable, with an evaluation of the mediating role of “human capital” development, and the commitment of employees in an academic environment. Six hundred questionnaires were randomly distributed to the employees of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 59 publications
7
150
0
14
Order By: Relevance
“…To this end, industry leaders customarily promote a bunch of work practices that have become known as HPWPs and involve aggregating a spectrum of HR strategies into a model of best practices [49]. In their recent research, Hamadamin and Atan [50] confirmed that strategic HRM practices are a significant and positive antecedent of sustainable competitive advantage.…”
Section: Hpwps Innovative Behavior and Competitive Advantagementioning
confidence: 99%
“…To this end, industry leaders customarily promote a bunch of work practices that have become known as HPWPs and involve aggregating a spectrum of HR strategies into a model of best practices [49]. In their recent research, Hamadamin and Atan [50] confirmed that strategic HRM practices are a significant and positive antecedent of sustainable competitive advantage.…”
Section: Hpwps Innovative Behavior and Competitive Advantagementioning
confidence: 99%
“…This study argues human capital theory as a mediation in SHRM research. Further, Hamadamin and Atan (2019) found partial effect of human capital on relationship between SHRM and competitive advantage. In this relationship of SHRM and performance, employees are considered as resources and knowledgeable.…”
Section: Propositions and Researchmentioning
confidence: 89%
“…Mainly they are based on employees' in-house training to develop suitable skills. However, HPWP are proved to provide results only in emerging economies, not in developed ones [17,18]. The employees' creativity and willingness to participate to the organization's outcomes are possible if the leadership is flexible and encourages a culture of lifelong learning, which should make a change in a person's attitude to work, especially in the decision-making process.…”
Section: Literature Reviewmentioning
confidence: 99%